Substrate-induced shifts and screening in the fluorescence spectra of supramolecular adsorbed organic monolayers - Kerfoot, James; Korolkov, Vladimir V.; Nizovtsev, Anton S.; Jones, Ryan; Taniguchi, Takashi; Watanabe, Kenji; Lesanovsky, Igor; Olmos, Beatriz; Besley, Nicholas A.; Besley, Elena; Beton, Peter H. (American Institute of Physics, 2018)
We have investigated the influence of the substrate on the fluorescence of adsorbed organic molecules. Monolayer films of perylene-3,4,9,10-tetracarboxylic-3,4,9,10-diimide (PTCDI), a supramolecular network formed from PTCDI and melamine, and perylene-3,4,9,10-tetracarboxylic-3,4,9,10-dianhydride (PTCDA) have been deposited on hexagonal boron nitride (hBN). The principal peaks in the fluorescence spectra of these films were red-shifted by up to 0.37 eV relative to published measurements for molecules in helium droplets. Smaller shifts (~0.03 eV) arising from interactions between neighbouring molecules are investigated by comparing the fluorescence of distinct arrangements of PTCDI, which are templated by supramolecular self-assembly and determined with molecular resolution using atomic force microscopy under ambient conditions. We compare our experimental results with red-shifts calculated using a combination of a perturbative model and density functional theory which account for, respectively, resonant and non-resonant effects of a dielectric hBN substrate. We show that the substrate gives rise to a red-shift in the fluorescence of an adsorbed molecule and also screens the interactions between neighbouring transition dipole moments; both these effects depend on the refractive index of the substrate.